DIFFERENCE OF pH AND CALCIUM LEVEL OF SALIVARYIN CARIES AND CARIES FREE STUDENTS OF FAKULTAS KEDOKTERAN GIGI UNIVERSITAS SUMATERA UTARA: PERBEDAAN VOLUME, pH DAN KADAR KALSIUM SALIVA KARIES DAN BEBAS KARIES PADA MAHASISWA FAKULTAS KEDOKTERAN GIGI UNIVERSITAS SUMATERA UTARA - R, Lisna Unita; Nisak, Rahayu (TALENTA, 2016)
Dental caries is a disease of hard tooth tissue in enamel, dentin and cementum, caused by bacterial activity that ferments carbohydrates leading to the dissolution of enamel due to acid produced by bacteria. Saliva contains protein, antibacterial, fluoride, calcium and phosphate ions that can protect teeth from caries. Balanced diet and adequate salivary flow will preserve to protect and maintain the health of hard tooth tissue. The caries process begins with Streptococcus mutants fermenting carbohydrates to form acids that produced a low pH of oral cavity. Low concentrated calcium in saliva can increase caries risk. The purpose of this study was to determine the volume, pH and saliva’s calcium level in caries and caries-free (control group) students of Fakultas Kedokteran Gigi Universitas Sumatera Utara. The research was an observational analytic study with cross-sectional design. The saliva studied was stimulated whole saliva taken from 46 subjects, 23 were caries and 23 were caries-free. Subjects were instructed to chew paraffin wax for 5 minutes and spitting the saliva into the pot. The examination to determine salivary volume was conducted in Laboratories of Oral Biology and Fakultas Farmasi Universitas Sumatera Utara. The result of this study showed the mean value of salivary volume in caries group is 3.55 ± 0.633 ml/5minutes and caries-free is 6.94 ± 1.482 ml/5 minutes, caries saliva pH 5.26 ± 0.219 and caries-free 6.68 ± 0.362, and calcium saliva caries 0.98 ± 0.310 mmol/L and caries-free 1.55 ± 0.312 mmol/L. There was a significant difference (p < 0.05) between the caries group and caries-free in volume, pH and salivary calcium levels. The conclusion of this research is the caries group has lower volume, pH and calcium level of saliva than non caries group.